Late-onset galactorrhea and menometrorrhagia/menorrhagia with venlafaxine use in migraine: a case report - Berilgen, M. S. (Springer Heidelberg, 2010)
[Abstract Not Available]
20th Meeting of the European-Neurological-Society -- JUN 19-23, 2010 -- Berlin, GERMANY